2014
DOI: 10.15274/inr-2014-10093
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Changes in Infantile Dissecting Anterior Communicating Artery Aneurysm Treated Endovascularly

Abstract: Intracranial aneurysms are extremely rare in infants, and to our knowledge only seven infants treated for ruptured spontaneous dissecting aneurysms have been reported. Good outcomes have been achieved with endovascular treatment of infantile aneurysm. We the endovascular treatment of a one-month-old girl for ruptured dissecting aneurysm located in the anterior communicating artery, and the unique radiological changes that were observed during the perioperative and follow-up periods. These changes sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, there have been reports of infants presenting with bleeding aneurysms following a precipitous delivery or non-accidental injury. [2][3][4][5][6][7][8][9][10][11][12][13][14][15]28 Among paediatric patients, age younger than 5 years and lesions located in the dorsal artery of the brainstem are independent risk factors for IA rupture, whereas an IA with a wide neck serves as a protective factor. 29 Moreover, the risk factors for IA in paediatric patients are distinctly different from those in the adult population, and its pathogenesis cannot be extrapolated from adult series.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been reports of infants presenting with bleeding aneurysms following a precipitous delivery or non-accidental injury. [2][3][4][5][6][7][8][9][10][11][12][13][14][15]28 Among paediatric patients, age younger than 5 years and lesions located in the dorsal artery of the brainstem are independent risk factors for IA rupture, whereas an IA with a wide neck serves as a protective factor. 29 Moreover, the risk factors for IA in paediatric patients are distinctly different from those in the adult population, and its pathogenesis cannot be extrapolated from adult series.…”
Section: Discussionmentioning
confidence: 99%
“…Proportion of dissecting aneurysm is reported as 16–45% in children which is higher than general population, and there is a tendency for the rate of dissecting aneurysms to increase with younger age [ 5 , 8 , 12 , 13 ]. Ruptured ACA dissecting aneurysm, is particularly rare and is known to have a poor prognosis [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the proportion of dissecting aneurysms increases at younger ages due to disruptions or defects in the vascular lamina due to infections or congenital diseases. 10 , 11 ) In a recent study focusing on the risk of seizure in pediatric patients with IAs, it appeared that pediatric patients are at a higher risk of seizure in the case of SAH as compared to the adults. The advanced hypothesis for this is the vulnerability of the cortex in pediatric patients, and the increased prevalence of IA located in the MCA is associated with cortical hemorrhage.…”
Section: Discussionmentioning
confidence: 99%